2019
DOI: 10.31933/dijms.v1i1.28
|View full text |Cite
|
Sign up to set email alerts
|

Bank-Specific and Macroeconomic Determinants of Non-Performing Loans of Commercial Banks in Bangladesh

Abstract: The prime objective of this research is to identify the main determinants of non-performing loans in the commercial banking system of Bangladesh for the period 2011-2016 using panel data modeling. This paper uses balanced panel data method to examine both bank-specific (return on average assets, net loans to deposit ratio, bank size, cost-to-income ratio, and capital adequacy ratio) and macroeconomic (real GDP growth rate and inflation rate) variables. To attain the objectives, the present research analyzed hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Our findings are consistent with the scholarly and empirical findings that NPLs have a detrimental impact on bank profitability (Adhikary, 2006;Akinlo & Emmanuel, 2014;Khatun & Ghosh, 2019;Nsobilla, 2016;Stephen Kingu et al, 2018;Towhid et al, 2020), while goes against the results found by some scholars (Boahene et al, 2012;Chimkono et al, 2016;Widana et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are consistent with the scholarly and empirical findings that NPLs have a detrimental impact on bank profitability (Adhikary, 2006;Akinlo & Emmanuel, 2014;Khatun & Ghosh, 2019;Nsobilla, 2016;Stephen Kingu et al, 2018;Towhid et al, 2020), while goes against the results found by some scholars (Boahene et al, 2012;Chimkono et al, 2016;Widana et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Due to the negative association between NPLs and the economy and the substantial negative relationship between ROA, loan-deposit ratio, and inflation rate (Towhid et al, 2020). Therefore, this trend in NPLs should be controlled for the shake of the country's growth and development and overall economic stability and regulators can make NPLs less of a problem by changing a country's financial regulatory framework based on what they learn from studying how NPLs affect a country (Khatun & Ghosh, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, low economic activities, higher unemployment and inflation rates, weak monetary policy, and unstable financial system are the major macroeconomic situations that cause high NPLs. Towhid et al (2019) used panel data modelling to uncover the key factors contributing to non-performing loans in Bangladesh's commercial banking sector between 2011 and 2016. In order to investigate both bankspecific (return on average assets, net loans to deposit ratio, bank size, cost-to-income ratio, and capital adequacy ratio) and macroeconomic (real GDP growth rate and inflation rate) factors, this study used the balanced panel data approach.…”
Section: Empirical Reviewmentioning
confidence: 99%